The effects of high glucose condition on rat tenocytes in vitro and rat Achilles tendon in vivo - Ueda, Y. (Bone Joint Res, 2018)
OBJECTIVES: The aim of this study was to investigate the effect of hyperglycaemia on oxidative stress markers and inflammatory and matrix gene expression within tendons of normal and diabetic rats and to give insights into the processes involved in tendinopathy. METHODS: Using tenocytes from normal Sprague-Dawley rats, cultured both in control and high glucose conditions, reactive oxygen species (ROS) production, cell proliferation, messenger RNA (mRNA) expression of NADPH oxidase (NOX) 1 and 4, interleukin-6 (IL-6), matrix metalloproteinase (MMP)-2, tissue inhibitors of matrix metalloproteinase (TIMP)-1 and -2 and type I and III collagens were determined after 48 and 72 hours in vitro. In an in vivo study, using diabetic rats and controls, NOX1 and 4 expressions in Achilles tendon were also determined. RESULTS: In tenocyte cultures grown under high glucose conditions, gene expressions of NOX1, MMP-2, TIMP-1 and -2 after 48 and 72 hours, NOX4 after 48 hours and IL-6, type III collagen and TIMP-2 after 72 hours were significantly higher than those in control cultures grown under control glucose conditions. Type I collagen expression was significantly lower after 72 hours. ROS accumulation was significantly higher after 48 hours, and cell proliferation after 48 and 72 hours was significantly lower in high glucose than in control glucose conditions. In the diabetic rat model, NOX1 expression within the Achilles tendon was also significantly increased. CONCLUSION: This study suggests that high glucose conditions upregulate the expression of mRNA for NOX1 and IL-6 and the production of ROS. Moreover, high glucose conditions induce an abnormal tendon matrix expression pattern of type I collagen and a decrease in the proliferation of rat tenocytes. Cite this article: Y. Ueda, A. Inui, Y. Mifune, R. Sakata, T. Muto, Y. Harada, F. Takase, T. Kataoka, T. Kokubu, R. Kuroda. The effects of high glucose condition on rat tenocytes in vitro and rat Achilles tendon in vivo. Bone Joint Res 2018;7:362–372. DOI: 10.1302/2046-3758.75.BJR-2017-0126.R2